Investigation of the influence of finely dispersed solid substances of the atmospheric air on humans - Kozii, Ivan (Видавництво Львівської політехніки, 2022)
An analytical study of the impact of solids contained in the air of urban areas on human health was conducted. Based on the analysis of the database of the Organization for Economic Cooperation and Development and the State Statistics Service of Ukraine on the emissions of substances into the atmosphere, it was established that the effects of solids on humans depend on particle diameter, morphological and physicochemical characteristics. The analytical research has shown that suspended airborne substances primarily damage the respiratory system and cause harm to the human cardiovascular system. The forecast model of emissions of finely dispersed suspended solids (PM2.5 and less) in Ukraine until 2030 was obtained. The critical analysis of indicators of admissible levels of pollution, considering the comparative characteristic of foreign and domestic standards of admissible concentration of suspended solids in the atmospheric air of settlements, was carried out.
Keywords: fine particles; emissions; atmosphere; pollution; diseases